Problem Based Learning (PBL) and Verbal-visual Abilities: Its Influence on Students’ Mathematics Learning Outcomes - Yudistira, Pengki; Syaiful, Syaiful; Anggareini, Evita (Universitas Islam Negeri Raden Intan Lampung, 2020)
This quasi-experiment aims to determine the influence of the Problem Based Learning (PBL) model and verbal-visual abilities on Grade VIII students’ learning outcomes. The population in this study were all students of SMPN 7 Kerinci and the sample of the study was 27 students from class VIII A as the experimental class and 26 students from class VIII B as the control class. Research data collection through test instruments to see students’ mathematics learning outcomes. Statistical analysis using two-way ANOVA with SPSS 21 software with a significance of 0.05. The results showed that there was an influence of the Problem Based Learning (PBL) model and verbal-visual ability on the mathematics learning outcomes of Grade VIII students with sig. 0,001 less than 0,005, there is an influence of verbal-visual ability on mathematics learning outcomes of class VIII students with sig. 0,000 less than 0.05 and there is no interaction between the PBL model and verbal-visual ability in influencing students’ learning outcomes in class VIII with sig. 0.341more than 0.05.